Correlation of fine needle aspiration cytology with histopathological diagnosis in assessing breast lumps at a tertiary care hospital - George, Greeshma Ann; Antony, Philips (International Journal of Research in Medical Sciences, 2018)
Background: Breast cancer is one of the most common malignancies in women worldwide (22%) and India ranks the second after cervical cancer. The diagnostic accuracy of FNAC increases to 99% when it is combined with clinical and radiological examination. In this study, authors plan to correlate the cytological findings with histopathological examinations for breast lesions and determine the accuracy of fine needle aspiration cytology in the diagnosis of breast lesions. Methods: It is a retrospective study carried out in the Department of Pathology at a Tertiary Care Hospital. All the FNAC results of breast lesions during the one year period were collected. Gauge needle maximum of 3 passes were made and the slides were fixed in 70-80% alcohol and stained with routine haematoxylin and eosin stain. Results: Among 200 patients, 197 were females and 3 were males. Benign breast lesions were found in 158 cases; among which fibroadenoma was the commonest lesion. Malignancy was observed in 25 cases. Two cases of phyllodes tumour were incorrectly reported as fibroadenoma on cytology. Of 12 cases which were diagnosed to have atypical lesions, 4 cases were papillary neoplasm, and 8 cases were atypical ductal hyperplasia. Conclusions: This study concludes that breast FNAC is a reliable, easy, cheap and effective procedure for the diagnosis. It reduces the need of core needle biopsies and very well correlated with histopathological examination. FNAC differentiates non neoplastic from the neoplastic by which it reduces the patient’s anxiety and helps the surgeons in planning the mode of treatment.